(3QSGdI aj CMGOjK hYXjIs - (3eLghds ((3eMeO GdegOhjs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg QH GdYGdejf bGd GdfHj Udi Gddg Ydjg hSde ef bQC hMaX CQHYjf MOjKG ef CeJj SeGg Gddg aj GdSeGA hdjG haj GdCQV abjgGs
(3BNQgG (B:s
(3bGd GdfHj Udi Gddg Ydjg hSde (B" (3GdOfjG OGQ GdZhQ (B( (3cPG (B) (3hGdBNQI (B"s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdMOjK hGdeUWdMs